2014
DOI: 10.1080/07448481.2014.963109
|View full text |Cite
|
Sign up to set email alerts
|

Role of Virtues and Perceived Life Stress in Affecting Psychological Symptoms Among Chinese College Students

Abstract: This study clarified the positive role of virtues in stressful situations among Chinese undergraduates. The results benefit the college health professionals in attending strengths of their clients in practice both in Eastern and Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
34
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…15–17 Mental health issues are prevalent on college campuses, can be detrimental to overall academic performance and success, and frequently lead to student attrition. 15 In addition, mental health issues are linked to suicidal ideation, a growing public health concern, specifically on college campuses.…”
Section: Introductionmentioning
confidence: 99%
“…15–17 Mental health issues are prevalent on college campuses, can be detrimental to overall academic performance and success, and frequently lead to student attrition. 15 In addition, mental health issues are linked to suicidal ideation, a growing public health concern, specifically on college campuses.…”
Section: Introductionmentioning
confidence: 99%
“…The transactional model of stress and coping (Lazarus & Folkman, 1984) states that high character strengths are characterized by an ability to perceive less stress (Duan et al, 2015). A longitudinal study found that the students with high character strengths experience less academic-related stress throughout the semester and flourish after experiencing mild depression symptoms (Duan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This model emphasizes the interactions between personal characteristics and situational factors rather than objective stressors alone (Lazarus and Folkman, 1984). Cross-sectional and longitudinal studies demonstrated that individuals with positive qualities, such as caring, inquisitiveness, and self-control, often perceived limited stress and showed an improved mental well-being (Duan et al, 2015b; Duan, 2016b). Therefore, the role of positive qualities in stressful situation should be investigated.…”
Section: Introductionmentioning
confidence: 99%